IMPACTS, PATTERNS, INFLUENCING FACTORS AND POLICIES OF FUELWOOD EXTRACTION IN WAY KAMBAS NATIONAL PARK, INDONESIA - Rakatama, Ari (Indonesian Journal of Forestry Research, 2016)
Uncontrolled fuelwood extraction from conservation forest of Way Kambas National Park (WKNP) could threaten the existing forest. This paper studies the way to tackle the forest degradation in WKNP, with less negative impacts to the local people. Study was conducted by analysing existing data and maps of WKNP in terms of forest degradation, forest inventories, current policies, survey on how fuelwood is extracted, observation on fuelwood gatherers, fuelwood demand, and identification of further policy options. Results show that the most significant factors influencing the fuelwood extraction activity in WKNP are land ownership, followed by the distance to forest area, income level, the number of household members and age of household head. In the field, the fuelwood utilization is allowed by WKNP Authority, although it is formally forbidden.It was stated that fuelwood extraction in the area should be less than 2.89 ton/ha/year to maintain its sustainability, based on the mean WNKP forest tree annual increment. The fact shows that fuelwood extraction in WKNP reduces of forest biomass stock (1.06 tons/ha/year) and decreases species diversity index (from 3.05 to 2.45), species evenness index (from 1.06 to 0.91) and old-young tree ratio (from 1.29 to 1). Ecosystem quality reduction is mainly caused by destructive techniques in extracting fuelwood such as slashing, scratching cambium, and cutting trees.